Prognostic value of global longitudinal strain versus mitral annular plane systolic excursion in patients with ischemic heart failure. (25th November 2020) - Liu, D; Wagner, C; Hu, K; Lengenfelder, B; Ertl, G; Frantz, S; Nordbeck, P
Abstract: Background: Mitral annular plane systolic excursion (MAPSE) derived from M-mode echocardiography is a classical risk factor of clinical outcome in heart failure patients. Two-dimensional-echocardiography (2DE) derived global longitudinal strain (GLS) is also related to outcome in patients with heart failure. This study aimed to compare the prognostic performance between GLS and MAPSE in ischemic heart failure patients with reduced ejection fraction. We sought to test the hypothesis that GLS might be superior to MAPSE as a risk stratification marker in these patients. Methods: In total, 1277 ischemic heart failure patients with reduced left ventricular ejection fraction (LVEF<50%), referred to our department between 2009 and 2017, were included in this retrospective study. Offline standard echocardiographic measurements including MAPSE and GLS were performed. Average MAPSE of septal and lateral walls (MAPSE_Avg) was calculated. GLS was derived from the segmental averaging (18-segment) of the three apical views. All patients completed at least one-year clinical follow-up by telephone interview or clinical visit. The primary endpoint was defined as all-cause mortality or heart transplantation (HTx). Results: At baseline visit, mean age was 70±11 years and 79.6% were men. NYHA class III-IV were identified in 33.5% of patients. Coronary artery disease was confirmed by coronary angiography. 63.0% patients had a history of myocardial infarction, 32.1% underwent PCI, and 16.8% underwent coronary artery bypass grafting. Over a median follow-up period of 26 (14–39) months, 369 (28.9%) patients died and 5 (0.4%) underwent HTx. Median LVEF was 39% (32–45%), and there were 48.0% patients with LVEF between 40–49%, 32.3% patients with LVEF between 30–49% and 19.7% patients with LVEF <30%. MAPSE_Avg was 8.0 (6.5–10.0) mm and median GLS was −9.9% (−7.7 to −12.3%). Clinical covariates significantly associated with all-cause mortality in this cohort included age (HR=1.048), NYHA class III-IV (HR=1.800), AF (HR=1.567), diabetes (HR=1.262), dyslipidemia (HR=0.657), hyperuricemia (HR=1.861), peripheral vascular disease (HR 1.858), chronic respiratory diseases (HR=1.680), and renal dysfunction (HR=2.705). Multivariable Cox regression analysis showed that reduced MAPSE_Avg (<7mm, HR=1.431, 95% CI 1.146–1.786) and reduced GLS (<8.3%, HR=1.519, 95% CI 1.230–1.875) were independent predictors of all-cause mortality after adjustment of above-mentioned clinical confounders. ROC curves demonstrated that the predictive performance of all-cause mortality among LVEF, MAPSE_Avg, and GLS were similar (AUC=0.608, 0.601, and 0.616, respectively, all P<0.001). Conclusions: Both 2DE-guided GLS and MAPSE could provide additional prognostic information in ischemic heart failure patients with reduced LVEF. Prognostic performance of GLS, MAPSE, and LVEF is similar in ischemic heart failure patients with reduced LVEF. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The German Federal Ministry of Education and Research